The Application of Multiplate Resazurin Reduction Assay in The Screening for Anti-Mycobacterial Activity from Indonesian Medicinal Plants - Martha Sari; Gita Syahputra; Wien Kusharyoto (Indonesian Journal of Pharmacy, 2019)
Tuberculosis (TB) is an airborne illness generated by Mycobacterium tuberculosis (Mtb), also one of the prominent infectious killers of adults worldwide. There is a pressing need to expand novel anti-mycobacterial drugs because of the increasing resistance of pathogenic mycobacteria to existing antibiotics. Native compounds acquired from microbial resources and medicinal cultivars have played an essential part as the origin of TB medications. The microplate resazurin reduction assay (MRRA) is generally utilized to assess natural and synthetic compounds for anti-mycobacterial activity. In our work, the MRRA method was employed to evaluate the anti-mycobacterial activity of extracts from curative plants using Mycobacterium smegmatis and Mycobacterium bovis BCG and to compare them to rifampicin as an anti-mycobacterial drug. The optimized MRRA utilized 2% aqueous DMSO and 62.5 μg/mL resazurin as an indicator compound in 5% aqueous Tween 80. The optimal incubation time for M. smegmatis was 24 hours, and for M. bovis BCG was 48 hours. The methanolic plant extracts were acquired from various Indonesian medicinal plants known to have anti-mycobacterial activity. The MRRA method using M. smegmatis or M. bovis BCG as anti-mycobacterial targets offers a distinct advantage such as low-cost, rapid, and safe screening for anti-mycobacterial activity in a middle to high-through-put-format.